A.E. SNESAREV ABOUT PAMIR KYRGYZS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article analyzes the works of A.E. Snesarev related to the Pamirs. The concept of “Pamir” and the borders of the Pamirs, as defined by local residents and ancient travelers, are considered. Historical and geographical overview of the Pamirs. Brief description of the Western and Eastern Pamirs. Number, characteristics of nomadic life and economy, food, physical type, beliefs, tribal divisions and settlement, administrative structure of the Kyrgyz of the Eastern Pamir.
Keywords: A.E.Snesarev, Pamir, Alichur, Murghab, Rangkul, Pamir Kyrgyz, teit, naiman.